Analisis Faktor-Faktor Yang Mempengaruhi Minat Belajar Tata Rias Dalam Kegiatan Ekstrakurikuler Beauty Class Pada Siswi SMA Berkebutuhuan Khusus Di SLB 02 Lenteng Agung Jakarta Selatan - Aprilia Youdhiyan Maritie; Elvyra Yulia; Dwi Atmanto (Journal on Education, 2024)
The purpose of the study is to analyze the factors that affect the interest in learning cosmetology in beauty class activities in high school students with special needs at SLBN 02 Lenteng Agung South Jakarta, This study is a quantitative research with the results of a hypothesis between variables X (factors that affect learning interest) and Y (interest in learning cosmetology) obtained the results of the t-test has a hypothesis test result which shows a significance value of 0.001 i.e. ≤ 0.05 shows that Ho is rejected and Ha is accepted, which means that there is a significant positive influence between factors that affect learning interest in cosmetology. The result of the determination coefficient (R2) is 0.953 which means that learning interest factors play a role of 95.3% in the interest in learning cosmetology. The remaining 4.7% was influenced by other variables that were not studied in this study. The results of this study concluded that the indicator that got the highest score from the X variable (factors that affect learning interest) was the "attention" indicator of 23.31% and from the Y variable (interest in learning cosmetology) got the highest score, namely the indicator of "general attitude towards activities" of 39.23%.